2005
DOI: 10.1177/1087057105277234
|View full text |Cite
|
Sign up to set email alerts
|

NanoStore: A Concept for Logistical Improvements of Compound Handling in High-Throughput Screening

Abstract: Small molecule screening, the systematic encounter of biology space with chemical space, has provoked the emergence of a whole industry that recreates itself by constant iterative improvements to this process. The authors describe an approach to tackle the problem for one of the most time-consuming steps in the execution of a screening campaign, namely, the reformatting of high-throughput screening test compounds from master plates to daughter assay plates used in the execution of the screen. Through an engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A key element of Evotec's fragment compound handling for high concentration bioassays is the application of the NanoStore concept that was co-developed by Pfizer and Evotec scientists [26]. The original purpose of NanoStore was to logistically uncouple the compound handling from the wet screening process in HTS.…”
Section: Evoscreen™ Detection Technologymentioning
confidence: 99%
“…A key element of Evotec's fragment compound handling for high concentration bioassays is the application of the NanoStore concept that was co-developed by Pfizer and Evotec scientists [26]. The original purpose of NanoStore was to logistically uncouple the compound handling from the wet screening process in HTS.…”
Section: Evoscreen™ Detection Technologymentioning
confidence: 99%
“…To explore the performance of a novel compound dry-down procedure, 4 we carried out a concordance experiment using neutral endopeptidase as a test system. The relative output from screening a file subset was used as a measure of success.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent experiments were consistent with this conclusion. 4 In addition to facilitating this understanding, the model has also allowed for a range of conditions to be readily explored that have led to the design of more efficient experiments for any future work. For example, we have concluded that screens should be used that will meet the dual need for a relatively high number of actives in the screened population (> 0.1%) and that also display activities spanning the range of percent effects of interest (e.g., 40%-100%).…”
Section: Discussionmentioning
confidence: 99%
“…GSK has undertaken various experiments to investigate the reconstitution of dried compounds of diverse chemical properties. Initial testing with 2-hydroxypropyl-βcyclodextrin excipient 18,19 with a small number of compounds did not show improved compound resolubilization of dried-down compounds (data not shown). Further experiments will be needed for more conclusive results with various other excipients.…”
Section: Compound Reconstitution Experimentsmentioning
confidence: 96%